2015
DOI: 10.1038/srep14806
|View full text |Cite|
|
Sign up to set email alerts
|

Stabilization of SIRT7 deacetylase by viral oncoprotein HBx leads to inhibition of growth restrictive RPS7 gene and facilitates cellular transformation

Abstract: Sirtuin-7 (SIRT7) deacetylase exhibits a high selectivity for acetylated H3K18 and has been implicated in the maintenance of malignant phenotype. However, it remains unclear if SIRT7 and H3K18ac play a role in the tumorigenic program driven by oncogenic viruses. We show that ectopically expressed HBx oncoprotein of hepatitis B virus promoted intracellular stability of SIRT7 by salvaging it from ubiquitin-mediated proteasomal degradation. HBx-dependent accumulation of SIRT7 favored H3K18 deacetylation and down-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…It has been observed that HBx oncoprotein of hepatitis B virus (HBV) stabilizes SIRT7 and stimulates H3K18 deacetylation, and depletion of SIRT7 decreases cell viability and transformation. These findings show that SIRT7 is an important regulator of HBx-driven oncogenic transformation [112]. In other research, high expressions of SIRT7 and H3K18Ac in hepatocellular carcinoma (HCC) were associated with worse patient overall survival (OS), and H3K18Ac levels turned out to be an independent prognostic factor in multivariate analysis.…”
Section: H3k18ac As a Biomarker In Cancer Progressionmentioning
confidence: 78%
“…It has been observed that HBx oncoprotein of hepatitis B virus (HBV) stabilizes SIRT7 and stimulates H3K18 deacetylation, and depletion of SIRT7 decreases cell viability and transformation. These findings show that SIRT7 is an important regulator of HBx-driven oncogenic transformation [112]. In other research, high expressions of SIRT7 and H3K18Ac in hepatocellular carcinoma (HCC) were associated with worse patient overall survival (OS), and H3K18Ac levels turned out to be an independent prognostic factor in multivariate analysis.…”
Section: H3k18ac As a Biomarker In Cancer Progressionmentioning
confidence: 78%
“…Adenoviral as well as SV40 virus infection leads to hypoacetylation of H3K18Ac. A recent report shows that H3K18Ac is downregulated upon HBV infection[23]. Thus LPS treatment which further restores the H3K18Ac status could be an ideal futuristic anti-viral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-based assays PR-619 was shown to substantially inhibit the activity of ubiquitin-specific protease, ubiquitin carboxy-terminal hydrolase, OTU, and MJD class DUBs when applied at 20–50 µ M, and exhibited a clear effect at a concentration as low as 5 µ M (Altun et al, 2011). PR-619 has been employed as a tool to investigate the role of ubiquitination in cellular processes including lysosomal degradation (Balut et al, 2011), caspase activation (Crowder et al, 2016), the stability of sirtuin-7 (Pandey and Kumar, 2015), protein aggregate formation (Seiberlich et al, 2012), human immunodeficiency virus replication (Setz et al, 2017), and oocyte maturation (Wang et al, 2017), as well as in the analysis of ubiquitin chain structure (Rana et al, 2017). In addition, PR-619 also inhibited the de-SUMOylating enzyme sentrin-specific protease (SENP) 6 in vitro and leads to accumulation of SUMOylated proteins in cells (Altun et al, 2011; Barry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%